Ensino de educação física na perspectiva do desenho universal para a aprendizagem: contribuições para a inclusão escolar - Braz, Aline Basso (Universidade Federal de São Carlos, 2025)
Although the literature indicates an increase in the number of studies related to the theme of Physical Education (PE) and inclusion, difficulties in enabling the implementation of school inclusion persist. In this sense, it is important to provide Physical Education teachers with support and knowledge regarding strategies that enable the participation and learning of all students. Given the above, the objective of the study is to analyze whether a school Physical Education teaching program based on the principles of universal design for learning (UDL) meets the needs of a group of students who learn together in diversity. The specific objectives are: to verify the multiple means of engagement, the multiple means of representation, and the multiple means of action and expression used during the PE teaching program; and to verify whether the PE teaching program based on the principles of UDL allows the participation and involvement of students with disabilities in classes. A qualitative research was conducted, characterized as field research, of the program evaluation type, developed in a school of the regular education network in a medium-sized city in the interior of São Paulo. Students enrolled in two second-year elementary school classes that have two students with intellectual disabilities participated. The data collection technique used in this research was systematic observation (field diary and the Assessment Protocol of the Principles of UDL applied to Physical Education - PADUA-EF). The Physical Education program based on the principles of UDL (PEF-DUA) lasted one academic semester and had three weekly classes of 50 minutes each. The field diaries were filled out by the researcher during the application of the PEF-DUA and the observations were made through the analysis of the filming of the program classes. The treatment of the data from the field diaries was based on thematic analysis and the observations on descriptive analysis. The application of the Physical Education teaching program (PEF-DUA), structured based on the principles of Universal Design for Learning (UDL), proved to be effective in promoting a more accessible school curriculum, including in classes composed of students with intellectual disabilities. The program consistently incorporated the three principles of UDL, favoring the engagement and active participation of all students in the proposed activities. Although challenges such as limited class time, lack of material resources and poor infrastructure were faced, careful pedagogical planning was essential for the successful implementation. The findings reveal that the principles of UDL can be successfully adapted to the context of school Physical Education, contributing to the creation of more inclusive environments. The study also highlights the importance of expanding future research, applying the PEF-DUA in contexts involving different types of disabilities, in order to evaluate its effectiveness in more diverse situations.
Teaching physical education from the perspective of universal design for learning: contributions to school inclusion
Keywords: Educação especial; Educação física escolar; Desenho universal para a aprendizagem; Inclusão escolar; Special education; Universal design for learning; School inclusion; Physical education; CIENCIAS DA SAUDE::EDUCACAO FISICA; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL